Endogenous Expression of the Human CD83 Attenuates EAE Symptoms in Humanized Transgenic Mice and Increases the Activity of Regulatory T Cells - Zinser, Elisabeth; Naumann, Ronald; Wild, Andreas B.; Michalski, Julia; Deinzer, Andrea; Stich, Lena; Kuhnt, Christine; Steinkasserer, Alexander; Knippertz, Ilka (Frontiers in Immunology, 2019)
The CD83 is a type I membrane protein and part of the immunoglobulin superfamily of receptors. CD83 is involved in the regulation of antigen presentation and dendritic cell dependent allogeneic T cell proliferation. A soluble form of CD83 inhibit dendritic cell maturation and function. Furthermore CD83 is expressed on activated B cells, T cells and in particular on regulatory T cells. Previous studies on murine CD83 demonstrated this molecule to be involved in several immune-regulatory processes, comprising that CD83 plays a key role in the development und function of different immune cells. In order to get further insights into the function of the human CD83 and to provide preclinical tools to guide the function of CD83/sCD83 for therapeutic purposes we generated Bacterial Artificial Chromosomes (BAC) transgenic mice. BACs are excellent tools for manipulating large DNA fragments and are utilized to engineer transgenic mice by pronuclear injection. Two different founders of BAC transgenic mice expressing human CD83 (BAC-hCD83tg mice) were generated and were examined for the hCD83 expression on different immune cells as well as both the in vitro and in vivo role of human CD83 (hCD83) in health and disease. Here, we found the hCD83 molecule to be present on activated DCs, B cells and subtypes of CD4+ T cells. CD8+ T cells, on the other hand, showed almost no hCD83 expression. To address the function of hCD83, we performed in vitro mixed lymphocyte reactions (MLR) as well as suppression assays and we used the in vivo model of experimental autoimmune encephalomyelitis (EAE) comparing wild-type and hCD83-BAC mice. Results herein showed a clearly diminished capacity of hCD83-BAC-derived T cells to proliferate accompanied by an enhanced activation and suppressive activity of hCD83-BAC-derived Tregs. Furthermore, hCD83-BAC mice were found to recover faster from EAE-associated symptoms than wild-type mice, encouraging the relevance also of the hCD83 as a key molecule for the regulatory phenotype of Tregs in vitro and in vivo.